Emulsifier ratio and shock treatment effect on the characteristics of eucalyptus–peppermint oil-based mouthwash nanoemulsion - Christina Winarti, Atika Hamaisa, Susi Lesmayati, Misgiyarta Misgiyarta, Gusmaini Gusmaini (Journal of Applied Pharmaceutical Science, 2024)
Eucalyptus oil, the main active ingredient in eucalyptol, is usually used in health products, but studies using eucalyptus oil in the form of nanoemulsions combined with peppermint oil have not been widely conducted. This study examined the influence of emulsifier ratios on nanoemulsion formulations of mouthwashes containing eucalyptus and peppermint oil. The ratios of emulsifiers (Tween 80 and PEG 400) used are 5:0, 4:1, 3:2; 2:3, 1:4, and 0:5. The parameters observed were particle size, turbidity, pH, refractive index (RI), stability, and inhibition against Staphylococcus aureus bacteria. The results showed that the best ratio of Tween and PEG provided a higher clarity value with a smaller particle size. Stability measurements revealed no separation of the resulting emulsion, and the physical properties changed only slightly when exposed to low and high temperatures. The pH of the emulsion for all formulas ranged from 5.61 to 5.91. The findings of the inhibitory test against S. aureus revealed that eucalyptus oil treatment generally showed no inhibition except for F5 (1:4) and F6 (0:5) treatment. The best treatment based on physicochemical characteristics is the ratio of Tween:PEG = 3:2.
Keywords: Eucalyptus citriodora, mouthwash, nanoemulsion, peppermint oil